INFORMATION SECURITY IN UKRAINE. CONTEXT OF NORMATIVE LEGAL SUPPLY - Kunchenko-Kharchenko, V. I.; Panasko, O. M. (Вісник Черкаського державного технологічного університету, 2018)
In view of the rapid information technologies development, intensive implementation of infor-mation and telecommunication systems in various spheres of state’s activity, modern world trends in information society, there is a need to consider the concept and content of information security. Due to the fact that today a number of main threats to the state's information security are realized in cyber-netic space, special attention should be paid to the notion of cybernetic security as an independent component of Ukraine's national security in relation to the sphere of information security and its legal security. In the article an analysis of the current state for regulatory of information security is made from the point of view of an integrated approach, such as general requirements to information securi-ty, requirements to the security of information infrastructure and security requirements of information technologies.